2013
DOI: 10.1186/1471-2369-14-246
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with 24-hour urinary volume: the Swiss salt survey

Abstract: BackgroundLow 24-hour urine volume (24UV) may be a significant risk factor for decline in kidney function. We therefore aimed to study associated markers and possible determinants of 24UV in a sample of the Swiss population.MethodsThe cross-sectional Swiss Salt Study included a population-based sample of 1535 (746 men and 789 women) individuals from three linguistic regions of Switzerland. Data from 1300 subjects were available for the present analysis. 24UV was measured using 24-hour urine collection. Determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
4
13
1
Order By: Relevance
“…We noted that 24-hour urine volume was associated with 24-hour urine creatinine in this study. A related study reported an association between 24-hour urine volume and creatinine clearance [33]. In contrast, our study did not find any association between 24-hour urine creatinine and creatinine clearance.…”
Section: Daily Urine Creatinine Excretion Associated With Daily Urinecontrasting
confidence: 99%
“…We noted that 24-hour urine volume was associated with 24-hour urine creatinine in this study. A related study reported an association between 24-hour urine volume and creatinine clearance [33]. In contrast, our study did not find any association between 24-hour urine creatinine and creatinine clearance.…”
Section: Daily Urine Creatinine Excretion Associated With Daily Urinecontrasting
confidence: 99%
“…[ 21 ], respectively. In this work, a total of 1.87 L urine was collected as 24-hour urine volume and was in the normal excretion range according to sex and age [ 32 ]. DON was quantified at 17.5 ± 2.7 µg/g creatinine ( n = 3) (equivalent to 18.8 ± 3.5 µg/L).…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Therefore, 2.5 and 97.5 centiles of the 24-hour creatinine excretion were calculated for each reference individual using a linear regression model with sex, BMI, and age as predictor variables recently published with data derived from the cross-sectional Swiss Salt Study (SSS). 46,47 The SSS includes a random population-based, cross-sectional sample of 1535 individuals, and the linear regression model was validated in 994 participants from the SKIPOGH study. 47 In this study, completeness of 24-hour urine collections was assumed if the total 24-hour creatinine excretion was within centiles 2.5 and 97.5, as described previously.…”
Section: Study Populationmentioning
confidence: 99%